The second trial of William Hone, on an ex-officio information, at Guildhall, London, December 19, 1817, before Lord Ellenborough and a special jury, for publishing a parody, with an alleged intent to ridicule the Litany, [...] (Hone, 1817)
In: The three trials of William Hone, [...]. PAMPHLET VOLUME.